Community-level physiological profiling of carbon substrate metabolization by microbial communities associated to sediments and water in karstic caves from Romania - PANAIT, Diana Felicia; PANAIT, Andrei Marian; CRISTEA, Adorján; LEVEI, Erika Andrea; MOLDOVAN, Oana Teodora; BANCIU, Horia Leonard (Studia Universitatis Babeș-Bolyai Biologia, 2025)
Cave ecosystems comprise specialized microbial communities that play essential roles in biogeochemical cycles; yet their metabolic capabilities and ecological functions are not fully understood. As conventional cultivation techniques provide limited insights into the metabolic capabilities, methods based on direct functionality screening may improve our knowledge of cave microbial activity. In this study, the Community-Level Physiological Profiling (CLPP) based on Biolog® EcoPlate™ approach was applied to assess carbon (C) substrate utilization by microbial communities associated with 36 environamental samples collected from five karstic caves (Cloșani, Ferice, Leșu, Muierilor, and Topolnița) in Romania. Principal Component Analysis (PCA) and Generalized Additive Models (GAMs) statistics were employed to infer the patterns of C substrate metabolization and their environmental drivers. Environmental variables such as sodium (Na) and electrical conductivity (EC) significantly impacted C substrate utilization capabilities as indicated by both PCA and GAM. The latter analysis elucidated non-linear relationships between variables, such as EC, Na, and Mg, and microbial metabolic diversity indices. However, distinct C substrate utilization patterns were detected among sampled sites and chemical types. Unlike moonmilk samples where associated microbial communities appeared as exhibiting low C substrate utilization, the highest activity was shown in cave pool water samples with the associated microbial communities extensively consuming D-galacturonic acid and Tween 80. Conversely, substrates like L-threonine and α-ketobutyric acid showed limited utilization across all cave samples. Average Well Color Development (AWCD) and Shannon diversity indices indicated that microbial communities associated to samples from Cloșani and Muierilor caves demonstrated the highest metabolic diversity. Our findings suggested that metabolic profiling using Biolog® EcoPlate™ method combined with multivariate statistical methods might prove a suitable analysis approach to effectively screen for cave microbial functionality and the probable environmental drivers. Besides, this work distinguishes from similar studies by relying on GAM analysis to predict the environmental factors governing the microbially-mediated organic carbon degradation in subterranean ecosystems. Article history: Received 28 February 2025; Revised 30 April 2025; Accepted 18 May 2025; Available online 25 June 2025